Highspeed Aufnahmen an drehenden Wälzlagern zur kinematischen Untersuchung des WEC-Wälzlagerschadens - Zürcher, Manuel; Feuerecker, Jonas; Pohrer, Benjamin; Holweger, Walter; Späth, Christian; Knöthig, Volker; Schlücker, Eberhard (Tribologie und Schmierungstechnik, 2018)
White Etching Cracks still are an intensely discussed topic among experts. Due to a wide range of possible explanations, there is no final answer to the question why this structural change appears. In this work, bearings which are running under WEC conditions are filmed by a high speed camera to investigate the bearing kinematics. Additionally, the lubricant distribution in the bearing is also examined and brought into connection to the WEC development.<br
Keywords: Electric load; High-speed recording; Ball bearing; White etching crack; Lubricant volume flow; Slip